2015
DOI: 10.1177/0961203314558676
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled study adding high dose vitamin D to analgesic regimens in patients with musculoskeletal pain

Abstract: Adding 4000 IU of vitamin D for patients with musculoskeletal pain may lead to a faster decline of consecutive VAS scores and to a decrease in the levels of inflammatory and pain-related cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 43 publications
2
53
0
3
Order By: Relevance
“…Researchers have shown that women with 25OHD serum levels <20 ng/mL have a higher chance of developing pain (Table 2) (Hicks et al 2008, Heidari et al 2010. Several studies have indicated that vitamin D supplementation (Table 2) is effective in reducing complaints in specific or nonspecific musculoskeletal pain disorders (Schreuder et al 2012, Gendelman et al 2015, Yilmaz et al 2016, Ghai et al 2017. In a recent meta-analysis (Table 2), Wu and colleagues (Wu et al 2016) 3 months reduced pain in conditions such as myalgia, arthritis and chronic musculoskeletal pain.…”
Section: Vitamin D and Painmentioning
confidence: 99%
“…Researchers have shown that women with 25OHD serum levels <20 ng/mL have a higher chance of developing pain (Table 2) (Hicks et al 2008, Heidari et al 2010. Several studies have indicated that vitamin D supplementation (Table 2) is effective in reducing complaints in specific or nonspecific musculoskeletal pain disorders (Schreuder et al 2012, Gendelman et al 2015, Yilmaz et al 2016, Ghai et al 2017. In a recent meta-analysis (Table 2), Wu and colleagues (Wu et al 2016) 3 months reduced pain in conditions such as myalgia, arthritis and chronic musculoskeletal pain.…”
Section: Vitamin D and Painmentioning
confidence: 99%
“…There are several pieces of evidence supporting a role of vitamin D in pain control, both in observational29 35–38 and in interventional studies 39 40. In a recent randomised, double-blinded and placebo-controlled study in rheumatic patients with musculoskeletal pain, it was shown that vitamin D (4000 IU/day) for 3 months resulted in faster decline of consecutive visual analogue scale (VAS) scores and a decrease in the levels of inflammatory-related and pain-related cytokines 39.…”
Section: Vitamin D and Painmentioning
confidence: 99%
“…In a recent randomised, double-blinded and placebo-controlled study in rheumatic patients with musculoskeletal pain, it was shown that vitamin D (4000 IU/day) for 3 months resulted in faster decline of consecutive visual analogue scale (VAS) scores and a decrease in the levels of inflammatory-related and pain-related cytokines 39. We have shown, in a prospective observational study, that patients with 25OHD levels <50 nmol/L before starting on statin treatment had four times higher risk of developing muscular symptoms, including muscular pain, compared with individuals with 25OHD levels >50 nmol/L (RR 4.2; 95% CI 1.7 to 10.2; p <0.01) 36.…”
Section: Vitamin D and Painmentioning
confidence: 99%
“…Además del desenlace de dolor medido con la EAV, se evaluaron los niveles de citoquinas pro-inflamatorias. Se encontró que el grupo que recibió la VD logró una mayor disminución del dolor, necesitó menos terapia de rescate y los niveles de TNFa y PGE2 disminuyeron también en forma significativa, concluyen que la adición de la VD a pacientes con DME llevó a una disminución más rápida del dolor y de los niveles de varias citoquinas inflamatorias 31 .…”
Section: Evidencia a Favorunclassified